Multiphysics modeling, sensitivity analysis, and optical performance optimization for optical laser head in additive manufacturing - Yang, Jiaping (2021)
Optical laser head is a key component used to shape the laser beam and to deliver higher power laser irradiation onto workpieces for material processing. A focused laser beam size and optical intensity need to be controlled to avoid decreasing beam quality and loss of intensity in laser material processing. This paper reports the multiphysics modeling of an in-house developed laser head for laser-aided additive manufacturing (LAAM) applications. The design of computer experiments (DoCE) combined with the response surface model was used as an efficient design approach to optimize the optical performance of a high power LAAM head. A coupled structural-thermal-optical-performance (STOP) model was developed to evaluate the influence of thermal effects on the optical performance. A number of experiments with different laser powers, laser beam focal plane positions, and environmental settings were designed and simulated using the STOP model for sensitivity analysis. The response models of the optical performance were constructed using DoCE and regression analysis. Based on the response models, optimal design settings were predicted and validated with the simulations. The results show that the proposed design approach is effective in obtaining optimal solutions for optical performance of the laser head in LAAM.